A Sustainable Supplier Selection Model: Integrating AHP and GRA for Enhanced Performance Evaluation - Gede Ariadi; Antonius Surjo Abdi (Jurnal Ilmiah Akuntansi, 2025)
This research aims to provide solutions to the problem of selecting fertilizer suppliers with the best performance in enhancing the sustainable supply chain (SSC) for organic farmers. The current limitation in supplier evaluation lies in the reliance on evaluators' subjective familiarity, which, while effectual or technical in some cases, carries inherent risks due to personal biases and the absence of systematic analysis. To address this, the study proposes an integrated model combining the Analytic Hierarchy Process (AHP) and Grey Relational Analysis (GRA). AHP is used to determine the relative importance of evaluation criteria based on expert judgment, while GRA evaluates supplier alternatives against these weighted criteria under uncertain conditions. This integrated approach enables more informed, robust, and justifiable decision-making in complex scenarios. The findings reveal that farmer groups tend to prioritize fertilizer suppliers who offer high product quality, with an emphasis on economic criteria such as production costs and crop profitability, as well as environmental criteria including material recycling and hygiene. In contrast, other suppliers focus more on social aspects, such as product safety, but often lack sensitivity toward the health impacts of non-organic fertilizers on farmers. Theoretically, the integration of AHP and GRA provides a comprehensive framework for measuring, assessing, and selecting suppliers based on performance. From a practical standpoint, fertilizer suppliers are encouraged to develop products that align with economic priorities—such as affordable pricing—and environmental goals, including reducing harmful chemical content like pesticides. This, in turn, supports farmer groups in enhancing sustainable performance, improving social welfare, and ensuring a safer working environment.